A preliminary study on the incidence of fecal coliform bacteria and staphylococcus aureus in viands sold to U.P.V. Miagao constituents - Dignadice, Burt Gulmatico (1996.)
Randomly selected foods served by six food sources to U.P.V. Miag-ao campus constituents were analyzed for the presence of fecal coliforms and staphylococcus aureus.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Fecal coliforms; Saphylococcus aureus